Inhibition of Maillard Reaction of Kepok Banana Flour with Citric Acid - Legowo, Anang; Pramono, Yoyok; Hintono, Antonius; Setiani, Bhakti Etza; Nabila, Aulia; Handoko, Nisfa (Talenta Publisher, 2024)
Bananas are a type of climateric fruit that undergoes post-harvest ripening, so bananas are easily damaged and have a short shelf life. Kepok banana flour is one of the food diversification products that can increase add value of kepok bananas. The production of kepok banana flour produces brown flour, so the appearance of flour is less attractive. Research aimed to improve quality of kepok banana flour using citric acid. The experimental design used was a Completely Randomized Design (CRD) with 5 treatments and 4 replications. The treatments given were citric acid concentrations of 0%, 0.2%, 0.4%, 0.6%, and 0.8%(w/v). The results obtained were whiteness index values of 75.07%-78.20%, water content of 3.05%-3.55%, reducing sugar of 0.03%-0.012%, color of 1.76-2.16, aroma of 2.00-2.80, and overalls of 2.68-2.92. Increase in the citric acid concentration may increase the reducing sugar, whiteness index, and water content kepok banana flour. The best treatment in the study was a concentration of 0.8% among others.